Strategy, investment, behaviour and results - Richard Pettinger (Tourism & Management Studies)
The drives to make effective business decisions are essentially generated by the need for human (as opposed to professional or expert) comfort, and therefore informed and influenced by the need to make outcomes as predictable and assured as possible, and that those in key organisational and managerial positions turn to the behaviours that they have learned over the entire period of their lives, rather than to professional expertise, knowledge and influence that are available to them in their organisations. This comfort and assurance is in turn driven by the fact that it is corporate rather than personal resources that are at risk and so on the face of it ‘there is little that can go wrong’. This is much more comforting at a human level, and much less dependent on the expertise of others, than relying on emerging techniques and tools such as business and web analytics, which are harder to use professionally, and require dependence and trust at a human level. Influences on behaviour can be seen in the form of: - Bullying, pulling rank and using power of personality and position to get decisions through an implemented - Employing uncritical people in senior positions to reinforce comfort and assurance. Influences on decisions can be tracked through relating intended outcomes to actual results and then in turn evaluating the key drivers of the decisions present at the time. The conclusions are that a body of knowledge and understanding in this area needs to be developed and implemented. A body of learning and understanding is required to be brought to the fore, so that those who arrive in top senior and critical positions can undertake some specialist development in this critical area before taking key decisions based on their own preferences and personality and position.